Materi Ajar Membaca berbasis E-Book bagi Mahasisswa di Riau: Kebutuhan Pembelajaran Bahasa - Asnawi, Asnawi; Sukenti, Desi; Alber, Alber; Wahyuni, Sri; Etfita, Fauzul; Zulhafizh, Zulhafizh (Jurnal Sastra Indonesia, 2023)
The availability of reading teaching materials is very necessary in future learning. In today's learning, teachers are required to be more creative in creating interesting learning, but still pay attention to the characteristics of the nation's culture. Therefore, it is necessary to develop teaching materials for reading through humanist literacy based on e-books. The basic problem is currently the lack of availability of digitally integrated reading teaching materials. The problem in this study relates to the need for e-book-based humanist reading teaching materials. The purpose of this study is to find out the need for e-book-based string reading teaching materials. The research method used is descriptive method. The data of this research are the results of questionnaires, interviews and reflection results. These data were sourced from research respondents who were obtained randomly. Data analysis was carried out in an interactive reflective manner using TagCword and AntCont. The results of the study describe students and lecturers in Riau province need to develop e-book-based reading teaching materials. The content of the required material is material that is integrated with the Malay Teaching and Learning. The text orientation needed by students and lecturers in Riau province is a text that reflects the attitudes and behavior of the Malay people.